2004
DOI: 10.1038/nature02789
|View full text |Cite|
|
Sign up to set email alerts
|

Sirtuin activators mimic caloric restriction and delay ageing in metazoans

Abstract: Caloric restriction extends lifespan in numerous species. In the budding yeast Saccharomyces cerevisiae this effect requires Sir2 (ref. 1), a member of the sirtuin family of NAD+-dependent deacetylases. Sirtuin activating compounds (STACs) can promote the survival of human cells and extend the replicative lifespan of yeast. Here we show that resveratrol and other STACs activate sirtuins from Caenorhabditis elegans and Drosophila melanogaster, and extend the lifespan of these animals without reducing fecundity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
1,309
5
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,728 publications
(1,379 citation statements)
references
References 24 publications
38
1,309
5
13
Order By: Relevance
“…We found ten studies on flavonoids and lifespan studies in D. melanogaster. Three of them used single compounds such as the flavanol epicatechin and the flavonol fisetin (58)(59)(60) , the other seven studies were on cocoa powder, green tea extract, Ludwigia octovalvis extract, apple polyphenols, black tea extract (BTE) and BE (61)(62)(63)(64)(65)(66)(67) (Table 2).…”
Section: Flavonoids and The Lifespan Of Drosophila Melanogastermentioning
confidence: 99%
“…We found ten studies on flavonoids and lifespan studies in D. melanogaster. Three of them used single compounds such as the flavanol epicatechin and the flavonol fisetin (58)(59)(60) , the other seven studies were on cocoa powder, green tea extract, Ludwigia octovalvis extract, apple polyphenols, black tea extract (BTE) and BE (61)(62)(63)(64)(65)(66)(67) (Table 2).…”
Section: Flavonoids and The Lifespan Of Drosophila Melanogastermentioning
confidence: 99%
“…This raises the question of whether activation of sirtuins by STACs is as effective also in vivo where sirtuins probably work under V max conditions. In vivo evidence, however, comes from studies in S. cerevisiae and C. elegans which showed that resveratrol at concentrations of 10 µM in yeast and 100 µM in the nematode extended the life span in dependence on sir2 and sir-2.1, respectively Wood et al, 2004). Another critical point regarding the activation of sirtuins in mammals is the concentration needed to act as STAC since plasma levels of 10 µM or even higher are difficult to achieve.…”
Section: To Fool Biology To Fool Biology To Fool Biology To Fool Biolmentioning
confidence: 99%
“…They have been implicated in diverse biological events, such as aging, energy control, circadian clocks, and mitochondrial biogenesis (Baur, Ungvari, Minor, Le Couteur, & de Cabo, 2012; Preyat & Leo, 2013; Wood et al., 2004). Of them, Sirt2 is associated with mitotic structures, beginning with the centrosome in mitotic prophase, the spindle in metaphase, and the midbody during cytokinesis, presumably to ensure normal cell division (North & Verdin, 2007).…”
Section: Introductionmentioning
confidence: 99%